Development of Sensor Based Standing Board Jump Test Equipment - Parsaoran Simatupang; Sabaruddin Yunis Bangun; Nimrot Manalu (UNIB Press, 2022)
The purpose of this research is to produce a standing board jump sensor -based. This research was carried out on students of the sports science faculty in April 2022. The type of research used in this study was development research with a Research & Development (R&D) research design from Borg and Gall. This research was conducted with 9 stages of research, namely, (1) Research and information collecting, (2) Planning, (3) Develop preliminary form of product, (4) Preliminary field testing, (5) Main product revision, (6) Main field testing, (7) Operational product revision, (8) Operational field testing, (9) Final product revision. The population in this study using the students of the faculty of sports science. sampling technique used was purposive sampling with a Phase I trial of 20 FIK students and a Phase II trial of 30 FIK students in the soccer course. Furthermore, from the Phase I trial, which amounted to 20 people, it showed a figure of 96% with the Very Eligible, then from the Phase II trial, which amounted to 30 students, it showed a figure of 91% in the Very Eligible. So from the results of this study it can be concluded that the development of a standing board jump can be used to measure leg muscle power through a standing board jump. Based on the data obtained, the development of a standing board jump is declared feasible to be developed as a sensor-based standing board jump test tool.